2021
DOI: 10.1155/2021/1285372
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative Analysis of the Effects of the Anti-VEGF Drug and Glucocorticoid by Injection before the End of Vitrectomy for Proliferative Diabetic Retinopathy

Abstract: Objective. To explore the effects of the anti-VEGF drug and glucocorticoid by injection before the end of vitrectomy for proliferative diabetic retinopathy (PDR). Methods. Eighty PDR patients who underwent vitrectomy in our hospital (July 2020–June 2022) were selected as the research objects and randomized into group A (n = 40) and group B (n = 40) according to the order of admission. Before the end of surgery, group B was injected with glucocorticoid (triamcinolone acetonide) into the vitreous cavity, and gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Recent studies have shown that the perioperative application of anti-VEGF, before the end of vitrectomy, can also reduce intraoperative blood loss, reduce the level of VEGF, reduce the possibility of postsurgical complications, and improve ophthalmic parameters such as best corrected visual acuity, central macular thickness, and macular blood flow density [ 61 ].…”
Section: Developmentmentioning
confidence: 99%
“…Recent studies have shown that the perioperative application of anti-VEGF, before the end of vitrectomy, can also reduce intraoperative blood loss, reduce the level of VEGF, reduce the possibility of postsurgical complications, and improve ophthalmic parameters such as best corrected visual acuity, central macular thickness, and macular blood flow density [ 61 ].…”
Section: Developmentmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%